A new species of smooth-skinned Spinomantis frog (Anura: Mantellidae) from south-eastern Madagascar - Vences, Miguel; Köhler, Jörn; Glaw, Frank (Zootaxa, 2017)
We present molecular evidence for the presence of two species morphologically similar to Spinomantis bertini in Andohahela National Park, south-eastern Madagascar, differing by 5.5−6.3% pairwise DNA sequence divergences in the mitochondrial 16S rRNA gene. One of these was observed at higher elevations of ca. 1650 m above sea level, whereas the other was found at lower elevations of ca. 715 m a.s.l., close to the type locality of S. bertini (Isaka-Ivondro), and in one other location (Andreoky, ca. 1050 a.s.l.). We herein assign these low- to mid-elevation specimens to S. bertini based on their occurrence near the type locality and general agreement in colour pattern with the type specimen of Gephyromantis bertini Guibé, 1947. The high-elevation form is described as Spinomantis beckei sp. nov. based on its molecular divergence and reciprocal monophyly with respect to S. bertini, lower expression of greenish dorsal colour and less distinct frenal stripe. Based on a comparison of published call descriptions for S. bertini and our recordings of S. beckei, we hypothesize that S. bertini has a lower note repetition rate in advertisement calls. Molecular data suggest that the S. bertini species complex is more diverse than previously recognized, with at least two more candidate species identified: S. sp. Ca7 from Ranomafana National Park, and a newly identified candidate species S. sp. Ca12 from Pic d’Ivohibe Special Reserve.